The Bilingual Writer: A Stranger Among Their Own? - Belobrovtseva, Irina (Literatūra, 2025)
This article addresses the issue of literary bilingualism. Summarizing the disagreements among linguists regarding the content and boundaries of the concept of bilingualism, the article – focusing in its practical part on Estonian-Russian literary bilingualism – can, in the absence of similar studies, be considered a prolegomenon to the topic. The situation of Estonian-Russian and Russian-Estonian bilingualism as a whole has a specific character due to particular historical conditions. Contemporary Estonian-Russian literary bilingualism is examined through the works of two poets, Jaan Kaplinski (whose native language is Estonian) and Igor Kotjuh (whose native language is Russian), both of whom have repeatedly published literary works in both Estonian and Russian. Also considered is the prose writer Kalle Kasper, who, in 2017, made his literary debut in Russian with the novel Miracle. The following methods were used to achieve the research objectives: stylistic text analysis, interviews with bilingual writers, and analysis of bilingual authors’ texts for traces of substrate influence from Russian and Estonian languages and cultures.
Keywords: contemporary intercultural discourse; literary aspect of bilingualism; Estonian bilingual writers